2006
DOI: 10.4049/jimmunol.176.3.1465
|View full text |Cite
|
Sign up to set email alerts
|

Protein Vaccines Induce Uncommitted IL-2-Secreting Human and Mouse CD4 T Cells, Whereas Infections Induce More IFN-γ-Secreting Cells

Abstract: Mouse and human CD4 T cells primed during an immune response may differentiate into effector phenotypes such as Th1 (secreting IFN-γ) or Th2 (secreting IL-4) that mediate effective immunity against different classes of pathogen. However, primed CD4 T cells can also remain uncommitted, secreting IL-2 and chemokines, but not IFN-γ or IL-4. We now show that human CD4 T cells primed by protein vaccines mostly secreted IL-2, but not IFN-γ, whereas in the same individuals most CD4 T cells initially primed by infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
76
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 47 publications
17
76
0
Order By: Relevance
“…The high proportion of IL-2-producing CD4 ϩ T cells detected following HBVac immunization is in accordance with data reported recently indicating that protein vaccines induce uncommitted IL-2-secreting CD4 ϩ T cells, whereas infections induce more IFN-␥-secreting cells (28,29). However, the large proportions of TNF-␣-secreting cells observed following HBVac immunization indicate that CD4 ϩ T cells induced by protein vaccines also produce effector cytokines.…”
Section: Cd4supporting
confidence: 78%
“…The high proportion of IL-2-producing CD4 ϩ T cells detected following HBVac immunization is in accordance with data reported recently indicating that protein vaccines induce uncommitted IL-2-secreting CD4 ϩ T cells, whereas infections induce more IFN-␥-secreting cells (28,29). However, the large proportions of TNF-␣-secreting cells observed following HBVac immunization indicate that CD4 ϩ T cells induced by protein vaccines also produce effector cytokines.…”
Section: Cd4supporting
confidence: 78%
“…Nevertheless, systemically administered FljB, another Salmonella Typhimurium flagellin, has been administered to humans without notable inflammation-associated symptoms such as fever (56), although it is unclear what impact this has on IgA or mucosal responses. Furthermore, we and others have shown that soluble flagellin can induce Th2 responses, and these may help counter some of the inflammatory effects induced by flagellin on the innate immune system (21,22,28,57). Further evidence that flagellin may not produce overt local inflammation in the intestine is that during inflammatory conditions, CD103 + DCs are impaired at driving tolerogenic responses (58).…”
Section: Discussionmentioning
confidence: 99%
“…Thpp cells may be appropriate for temporarily suppressing acute antipathogen responses that are causing excessive pathology and, in addition, the Thpp cells would retain the potential to differentiate later into strong effector (e.g., Th1 or Th2) phenotypes (24,59). In contrast, Treg cells would be more suitable for long-term suppression of autoimmune anti-inflammatory responses, without the risk of future differentiation into effector cells.…”
Section: Discussionmentioning
confidence: 99%